Dynamic identification and continuous dynamic monitoring of bridges: different applications along bridges life cycle. Issue 4 (3rd April 2018) - Cunha, Álvaro; Caetano, Elsa; Magalhães, Filipe; Moutinho, Carlos
Abstract: This paper aims at stressing the major role that Dynamic Identification and Continuous Dynamic Monitoring can play in the observation and understanding of the structural behaviour of bridges along the different phases of their life cycle, based on the authors' experience got at the Laboratory of Vibrations and Structural Monitoring (ViBest) of the University of Porto during the last 20 years. The paper comprehends two initial sections summarising some relevant aspects regarding the evolution observed in terms of excitation devices and instrumentation, as well as in the field of modal identification of large Civil structures. Subsequently, the importance of dynamic identification along bridges' life cycle (design, construction, commissioning, and service or rehabilitation phases) is illustrated on the basis of relevant case studies, involving several outstanding structures. Lastly, the interest and potential of Continuous Dynamic Monitoring is also emphasised, describing several dynamic monitoring programmes implemented with different perspectives, such as: (i) the vibration serviceability safety checking in lively footbridges; (ii) the evaluation of dynamic effects of traffic loads in roadway and railway bridges and fatigue assessment; (iii) the vibration based damage detection; (iv) or the dynamic monitoring of wind effects on large bridges.